2017
DOI: 10.1007/s11099-016-0665-0
|View full text |Cite
|
Sign up to set email alerts
|

Gas-exchange parameters and morphological features of festulolium (Festulolium braunii K. Richert A. Camus) in response to nitrogen dosage

Abstract: The response of some photosynthetic parameters (CO 2 assimilation, transpiration rate, stomatal conductance, intercellular CO 2 concentration, water-use efficiency, and chlorophyll content), shoot development, and the morphological features of the root system to differentiated conditions of nitrogen supply was tested in festulolium (Festulolium braunii K. Richert A. Camus) varieties (Felopa and Sulino). Nitrogen fertilization with no nitrogen added [0 g(N)], single dosage [0.23 g(N)], and double dosage [0.46 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…Our results showed the highest values of crop water productivity and fruit water productivity in the N-200 and N-250 fertilized plants, confirming the important relationship between soil water content and N fertilization that was also reported in other studies [62,63]. In addition, similar results were reported by Mastalerczuk et al [64] on festulolium, confirming that lack of nitrogen results in lower values of water use efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed the highest values of crop water productivity and fruit water productivity in the N-200 and N-250 fertilized plants, confirming the important relationship between soil water content and N fertilization that was also reported in other studies [62,63]. In addition, similar results were reported by Mastalerczuk et al [64] on festulolium, confirming that lack of nitrogen results in lower values of water use efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…1 ). Research conducted by Mastalerczuk et al [ 31 ] and Borawska-Jarmujłowicz et al [ 32 ] on perennial ryegrass showed that significant reductions in chlorophyll contents were observed after subjecting seedlings to abiotic stresses. These findings are consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of suitable nutrients for the current growth phase and conditions of cultivation during plant vegetation are crucial for the normal physiological state of the plant as a whole, especially for the photosynthesis (Kalaji et al 2014, Mastalerczuk et al 2017. In this work, we investigated in vivo on three occasions the Chl a fluorescence transients at three leaf ages to analyze the changes in light-dependent phase of photosynthesis in nutrient-deficient Miscathus × gigantheus Anderss.…”
Section: Discussionmentioning
confidence: 99%